2010
DOI: 10.4103/0970-2113.63605
|View full text |Cite
|
Sign up to set email alerts
|

Anemia as a risk factor for childhood asthma

Abstract: Objective:This prospective-(cohort) study was conducted to evaluate whether anemia is a risk factor for childhood asthma.Materials and Methods:Two hundred children in the age group of 2-18 years who attended the Outpatient Department with upper respiratory / lower respiratory tract infections were included in this study. One hundred children with anemia were taken as the study group and another 100, age - and sex-matched children without anemia were taken as the control.They were subjected to complete blood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 6 publications
5
31
0
Order By: Relevance
“…Prevalence of iron defi ciency anaemia as per our criteria in present study was 32% in cases and 24% in control group, however, the diff erence was not signifi cant sta s cally though children with iron defi ciency anaemia were at a higher risk of wheeze associated respiratory diseases (OR=1.49; 95% CI 0.62-3.59). This fi nding is in agreement with the observa ons of workers such as Ramakrishnan and Borade in 2010, who reported higher prevalence of asthma among anaemic children as compared to non-anaemic children and also indicated a signifi cant associa on between iron-defi ciency anaemia and respiratory illness 10 .…”
Section: Discussionsupporting
confidence: 81%
“…Prevalence of iron defi ciency anaemia as per our criteria in present study was 32% in cases and 24% in control group, however, the diff erence was not signifi cant sta s cally though children with iron defi ciency anaemia were at a higher risk of wheeze associated respiratory diseases (OR=1.49; 95% CI 0.62-3.59). This fi nding is in agreement with the observa ons of workers such as Ramakrishnan and Borade in 2010, who reported higher prevalence of asthma among anaemic children as compared to non-anaemic children and also indicated a signifi cant associa on between iron-defi ciency anaemia and respiratory illness 10 .…”
Section: Discussionsupporting
confidence: 81%
“…17 Ramakrishnan and Borade found that anemia was a risk factor for childhood asthma. 18 Bard et al reported that anemia increased heart rate and cardiac output in BPD patients. 19 We first investigated the relationship between Hb levels in the first few days of life and BPD and the results may help us understand the complicated mechanism of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the factors identified in previous studies, we considered anemia status as one of the predictor variable. A cohort study conducted on children in age group 2-18 years concluded that anemia is a risk factor for childhood asthma [17]. Therefore, in order to study the impact of hemoglobin level on the onset of asthma among adults, we included this variable in the study.…”
Section: Discussionmentioning
confidence: 99%